Grégoire de Nysse et Julien l’Apostat. Polémique antipaïenne et identité chrétienne dans le Panégyrique de Théodore - Leemans, Johan (Revue d'études augustiniennes et patristiques, 2007)
The message conveyed by early Christian homilies served different purposes: didactic, parenetic, apologetic or polemic, to name just a few. This article shows that Gregory of Nyssa’s Panegyric on Theodore the Recruit (BHG 1760), delivered in 379/380, can be meaningfully interpreted as a polemical rejection of Julian the Apostate’s attempts to restore paganism in the early 360’s. After a general introduction on panegyrical sermons on martyrs (I) and a presentation of Gregory’s Panegyric on Theodore follows the argumentation which proceeds in three steps (II). Firstly, two elements of indirect proof are brought to the fore: a comparison with the Passion of Theodore (BHG 1761) indicates that the strong anti-pagan tendency in the sermon is due to Gregory himself and that it is a priori certainly reasonable to bring this in connection with Julian’s religious policy because many other patristic authors, some of them writing much later than Gregory of Nyssa, did the same (A). Secondly, it is shown how some passages in the homily, which contain a polemical rejection of paganism in its entirety, provide the foundation for the anti-Julianist polemic (B), which is then being analysed as the final step of the argument (C). In a final section it is explained how in these polemical passages the homilist did not only reject paganism and Julian’s policy but, in doing so, also strenghtened the Christian identity of his audience (III).